2011
DOI: 10.1210/jc.2011-1036
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the Early Life Programming of Serum Leptin Levels in European Adolescents: The HELENA Study

Abstract: These findings provide further evidence for a sex-specific programming effect of birth weight on serum leptin levels. Our results also contribute to explain the detrimental health effects associated with lower birth weight, such as long-term increased risk of developing obesity and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
2
5
0
1
Order By: Relevance
“…Birth weight was negatively associated with serum leptin concentrations only in female adolescents, providing additional evidence for a sex-specific programming effect of birth weight on the energy homeostasis control (10). We also showed that physical activity attenuates the negative effect of low birth weight on leptin concentrations in female adolescents (11).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Birth weight was negatively associated with serum leptin concentrations only in female adolescents, providing additional evidence for a sex-specific programming effect of birth weight on the energy homeostasis control (10). We also showed that physical activity attenuates the negative effect of low birth weight on leptin concentrations in female adolescents (11).…”
Section: Resultssupporting
confidence: 61%
“…Literature on lifestyle factors and diseases in European adolescents is scarce (6). Therefore, the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) 10 study aimed to investigate different lifestyle factors and health outcomes among European adolescents. The aim of this review is to summarize the main findings of the HELENA study related to the nutritional programming of adolescent nutritional diseases, dietary intake, physical activity, and vitamin status in European adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…For adolescent girls, our finding of an increased BMI throughout the total distribution may reveal a sex-specific obesogenic effect at the population level, and earlier studies have shown sex-related differences in weight gain due to both biological, behavioral and traumatic experiences [13, 3335]. Due to the limitations of the cross-sectional design and the lack of other body measurements and biological tests, we were not able to explore changes in important risk factors that could explain the shift in OWOB and BMI scores.…”
Section: Discussionmentioning
confidence: 52%
“…Herein, we found leptin levels to be elevated in female offspring at 5–6 months of age in the highest mixture dose (Mix-37.5%). Interestingly, this sexually dimorphic response to intrauterine exposure to xenobiotics is also seen in humans, where serum leptin levels were negatively associated with birth weight in adolescent girls, but not boys 18 . Conversely, in utero exposure to either butylparaben or di-isobutylphthalate lowers leptin and insulin levels in the rat 19 , albeit the latter was measured in the fetal compartment and thus not directly comparable to postnatal measurements.…”
Section: Discussionmentioning
confidence: 82%